Unisma Sports Center Building Project Control Analysis Using the Critical Path Method (CPM) - Ruli Saefudin; Ade Fitriyanti Ulul Azmi (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Islam Lamongan, 2024)
The purpose of this research is to determine the scheduling activities for the construction of the Sport Center Building at the Islamic University of Malang, to determine and analyze the control of building construction projects managed by the Islamic University of Malang using the CPM (Critical Path Method) method. This research uses the research method used in this research, namely the descriptive method. The data collection techniques used were observation, interviews, and library research. After obtaining information through interviews, data analysis was carried out using the CPM (Critical Path Method) method. The researcher has completed the research and from this analysis, the researcher found that the construction work carried out by the Islamic University of Malang required 180 days of work using the CPM (Critical Path Method) method, so the optimal duration of the project can be accelerated to 33 days so that the initial project duration is 196 days. working days to 163 days with an efficiency of 16,837%